Strategic business models field lab: analysis of the peer-to-peer business model in the Ota accommodation industry - recommendation: add-on services - Pêgas, Mariana Salgueiro Fernandes Gonçalves (2022)
Despite the harsh impact of the COVID-19 pandemic, the OTA Accommodation industry remains a growing and diverse environment. Utilizing Business Model Analysis as a guiding framework, this Field Lab Report provides insights into the evolution and variation of OTA Accommodation business models. The focus is then narrowed on the Peer-to-Peer Accommodation Model with an analysis of its main components, advantages, and vulnerabilities. Three detailed recommendations are ultimately proposed to strategically optimize this business model and address innovation opportunities. In this particular part, the proposed recommendation regards Add-On Services that P2P Accommodation platforms should take in consideration in order to protect their business model from unexpected shocks that might block international or domestic travel. To conclude, key insights and possible extensions are provided.